Effect of Mo interlayer on magnetic properties of exchange coupled Sm-Co/Fe bilayers - Shahzad,Furrukh (2010)
Sm-Co/Fe, hard/soft magnetic bilayers have been fabricated on 70 nm Cr buffered Si (100) substrate by dc and rf magnetron sputtering and annealed at 525O C for 30min. Very thin Mo layers (0-0.7 nm) were introduced between Sm-Co and Fe layers. The samples were analyzed by X-Ray Diffraction (XRD) and Alternating Gradient Magnetometer (AGM). All of the samples showed strong exchange coupling between hard and soft magnetic phases. Magnetization, coercivity and energy product (BH)max suggest a sinusoidal behavior. The energy product was found increased to 45% for 0.3 nm Mo interlayer as compared to sample without Mo layer.